Symmetric telecom regulation, competition and investment - Anders Henten; Morten Falch (International Telecommunications Society (ITS), 2019)
The paper aims at analyzing the implications of symmetric telecom regulation on competition and investment in the telecom area. Symmetric regulation, where it is not only the operators with significant market power (SMP) at national or large geographical scales which are subject to special access obligations, has been on the agenda for long. However, emphasis has hitherto been on asymmetric regulation, but during the past few years, symmetric regulation has gradually gained weight in different EU countries, and the new European Electronic Communications Code (Directive 2018/1972) also aims at putting more emphasis on symmetric regulation (de Streel and Larouche, 2016; Briglauer et al., 2017). The paper elaborates on the rules for the implementation of symmetric regulation in the Communications Code and discusses how symmetric regulation can potentially effect competition and investment. The assessment will look at the potential impacts of symmetric regulation on competition and discuss how competition can affect investment. The reason for this sequence of analysis is that it is assumed that the implications of symmetric regulation on investment, to a large extent, will be mediated by the implications of symmetric regulation on competition. However, symmetric regulation will also directly impact investment in the sense that the implementation of symmetric regulation may lower the incentives for physical infrastructure investment by new-coming network operators to a geographical area. It could also limit incentives for additional investment by operators that are already there with physical networks, as they may have to open their networks for other competing operators. But it could also lead to increased investments, which is the hope enshrined in the new European Communications Code of 2018...
Keywords: 330